2001
DOI: 10.1128/jvi.75.8.4002-4007.2001
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization and Vector-Specific Antagonist Activity of Domain III of the Tick-Borne Flavivirus Envelope Protein

Abstract: The molecular determinants responsible for flavivirus host cell binding and tissue tropism are largely unknown, although domain III of the envelope protein has been implicated in these functions. We examined the solution properties and antagonist activity of Langat virus domain III. Our results suggest that domain III adopts a stably folded structure that can mediate binding of tick-borne flaviviruses but not mosquito-borne flaviviruses to their target cells. Three clusters of phylogenetically conserved residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 18 publications
2
88
0
1
Order By: Relevance
“…Interestingly, in the E protein, the tripeptide (TGP) of ROCV within domain III was found to be different from those observed in all other JEV members (RGX, where X is D, E or T). As the RGD motif is speculated to be involved in the virus adsorption to host cells for JEV and MVEV, two important JEV group flaviruses (Bhardwaj et al, 2001;Lee & Lobigs, 2000) and as it was also found in ALFV and USUV, further experimental studies for ROCV are needed to investigate the role of the TGP tripeptide in the mechanisms that involve the viruscell interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the E protein, the tripeptide (TGP) of ROCV within domain III was found to be different from those observed in all other JEV members (RGX, where X is D, E or T). As the RGD motif is speculated to be involved in the virus adsorption to host cells for JEV and MVEV, two important JEV group flaviruses (Bhardwaj et al, 2001;Lee & Lobigs, 2000) and as it was also found in ALFV and USUV, further experimental studies for ROCV are needed to investigate the role of the TGP tripeptide in the mechanisms that involve the viruscell interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the E protein, the tripeptide (TGP) of ROCV within domain III was found to be different from those observed in all other JEV members (RGX, where X is D, E or T). As the RGD motif is speculated to be involved in the virus adsorption to host cells for JEV and MVEV, two important JEV group flaviruses (Bhardwaj et al, 2001;Lee & Lobigs, 2000) and as it was also found in ALFV and USUV, further experimental studies for ROCV are needed to investigate the role of the TGP tripeptide in the mechanisms that involve the viruscell interaction.The functional roles of the 39-NCR of flaviviruses have been recently studied and the roles in the genomic cyclization between the 59-and 39-NCRs, viral replication and translation were elucidated. Moreover, the putative changes in the highly conserved regions related to important biological functions of the flaviviruses (survival and/or pathogenicity) were recognized (Bryant et al, 2005;Khromykh et al, 2001).…”
mentioning
confidence: 99%
“…Importantly, a majority of the neutralizing epitopes have been mapped to the domain III region of the flavivirus E protein (8 -11). Furthermore, the WNV E DIII protein can be expressed as a recombinant protein that independently folds as an individual functional fragment and is capable of eliciting neutralizing Abs against WNV (12). Hence, the potential of WNV E DIII protein to function as an effective recombinant subunit vaccine against WNV is assessed and is presented in this study.…”
Section: W Est Nile Virus (Wnv)mentioning
confidence: 99%
“…DII contains a fusion loop at its distal end that is indispensable for virus-cell membrane fusion. The Ig-like C-terminal domain DIII undergoes a major, pH-triggered positional rearrangement essential for fusion, and may also be involved in receptor binding (2,(6)(7)(8)(9)(10)(11)(12). During cell entry of flaviviruses, low endosomal pH triggers a proposed E protein rearrangement cascade, including the dissociation of E dimers and the outward rotation of DII during the repositioning of E monomers into fusion-active trimers (6,9,13).…”
mentioning
confidence: 99%